Myocardial dysfunction induced by food restriction is related to calcium cycling and beta-adrenergic system changes - Gut, Ana Lúcia [UNESP]; Okoshi, Marina Politi [UNESP]; Padovani, Carlos Roberto [UNESP]; Aragon, F. F.; Cicogna, Antonio Carlos [UNESP] (Elsevier B.V., 2003)
Food restriction (FR) has been shown to promote myocardial dysfunction in rats. The aim of this study was to verify the participation of calcium and beta-adrenergic system on myocardial mechanical alteration in rats submitted to FR. Myocardial performance was studied in isolated left ventricular papillar muscle from young Wistar-Kyoto rats (WKY) submitted to FR or to control diet. The groups subjected to FR were fed 50% less food than the control group for 90 days. Mechanical function was studied in isometric contraction at post-rest contraction of 30 seconds (PRC), calcium chloride concentration 5.20 mM, and beta-adrenergic stimulation with isoproterenol 10(-6) M. FR decreased the body weight, and left and right ventricular weight. In basal condition (1.25 MM of calcium) time to peak tension (TPT) and time from peak tension to 50% relaxation (RT50) were greater in the FR group. Muscle function was. The same in both PRC groups. TPT decrease in both high calcium groups, more in FR rats; RT50 dropped only in FR animals. TPT decreased in both Isoproterenol groups, more intensely in the FR group. This result suggests that food restriction impairs myocardial performance and these changes may be attributed to alterations in the intracellular calcium cycling and beta-adrenergic system. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: food restriction; myocardium function; calcium; isoproterenol; papillary muscle; rat